Novel PILs (at) COF composite material and application performance

By assembling the two-dimensional iminotriazine COF material with polyionic liquid, functionalized ionic COF material is constructed, which solves the problem of using transition metals in the existing catalysts, and achieves efficient catalytic conversion of CO2 without a promoter, which is green and environmentally friendly and efficient.

CN119638910APending Publication Date: 2025-03-18TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311199674.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing catalysts have the disadvantage of using transition metals when promoting the cycloaddition reaction of CO2, which violates the principle of green chemistry. At the same time, the thermodynamic stability and kinetic inertia of CO2 limit their effective conversion.

Method used

By reasonably assembling the stable two-dimensional iminotriazine COF material with the cocatalyst polyionic liquid, a functionalized ionic COF material with stable structure, large specific surface area and high CO2 adsorption amount is constructed, and the efficient catalytic conversion of CO2 under mild conditions without cocatalysts is achieved.

Benefits of technology

The catalyst showed a high conversion rate for CO2 cycloaddition reaction and maintained good stability during the long-term catalysis process. It developed a multifunctional ionic COFs material with simple preparation technology, green and environmentally friendly and efficient preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a novel functionalized ionic liquid modified imino triazine COF composite material, which is prepared by grafting a functionalized polyionic liquid (PILs) containing a hydrogen bond donor, a nucleophilic group and the like to a two-dimensional imino triazine COF material with a stable structure by adopting an in-situ polymerization method. The material shows excellent catalytic performance in cycloaddition reaction of epoxy chloropropane and carbon dioxide, and under optimized process conditions, the epoxy chloropropane conversion rate can reach 94% or above, and the selectivity can reach 99% or above. Meanwhile, the novel triazine COF composite material has good universality on the cycloaddition reaction of the type. The cocatalyst-polyionic liquid is grafted to the COF material, efficient catalytic conversion of CO2 under the mild condition without a cocatalyst is achieved, and the method has remarkable application prospects and conforms to the concept of green development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite catalyst preparation and application, and in particular, relates to a preparation method of a COF-based composite material applied to CO2 cycloaddition reaction and its catalytic performance. Background of the Invention

[0003] Global warming, sea level rise, and ocean acidification have been plaguing us for many years. These environmental problems are mainly caused by the rising concentration of carbon dioxide in the atmosphere. At the same time, CO2 is considered to be a naturally abundant, renewable, and abundantly available C1 resource. Therefore, the conversion of CO2 into high value-added products through various methods has received widespread attention. One of the most attractive strategies is the atom-economic reaction of CO2 with epoxides to form cyclic carbonates. In addition, cyclic carbonates have a wide range of applications in polar aprotic solvents, lithium-ion battery electrolytes, polymer raw materials, etc. However, the thermodynamic stability and kinetic inertness of CO2 limit its effective conversion, so active catalysts are needed to promote the cycloaddition reaction of CO2.

[0004] In order to solve this problem, the immobilization of polyether imidazolium ionic liquids on ZSM-5 zeolite was studied, and imidazolium-based PIL was incorporated into MIL-101. However, this catalyst cannot avoid the use of transition metals, which may violate the principles of green chemistry. Therefore, it is necessary to design a new metal-free catalyst to overcome the above shortcomings. Covalent organic framework (COF) materials have the characteristics of high crystallinity, large specific surface area, low density and easy modification, which are favored by researchers. The presence of imine groups in two-dimensional imine-based COF materials can adsorb and activate CO2, thereby improving the capture capacity of CO2. Polyionic liquids have the advantages of hydrogen bond donors and nucleophilic anions, which can activate epoxides and promote ring opening. Therefore, the stable two-dimensional imino triazine COF material and the co-catalyst polyionic liquid are rationally assembled to realize the CO2 cycloaddition reaction without co-catalyst and under mild conditions. This invention is expected to develop a multifunctional ionic COFs material with simple preparation process, green environmental protection and high efficiency, and realize the efficient catalytic conversion of CO2 without co-catalyst and under mild conditions. Summary of the invention

[0005] The present invention provides a preparation method and catalytic application of a novel COF catalyst, using a two-dimensional iminotriazine COF material as a carrier, and through an ionic liquid modification strategy, constructing a functionalized ionic COF material with stable structure, large specific surface area and high CO2 adsorption capacity, and investigating its catalytic performance for CO2 cycloaddition reaction. The catalyst has a high conversion rate for CO2 cycloaddition to cyclic carbonate, and maintains good stability during a long catalytic process.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0007] The specific implementation plan is as follows:

[0008] The present invention proposes a novel PILs@COF composite material, the structural formula of which is shown below:

[0009]

[0010] R is one of -NH2, -COOH, -OH and -H, and X is Br. The composite material exhibits good catalytic performance on the cycloaddition reaction of epoxy compounds and carbon dioxide.

[0011] Among them, a method for preparing a PILs@COF composite material comprises the following steps:

[0012] (1) Preparation process of Vinyl-COF material:

[0013] 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine are mixed and then added into a mixed solvent, and a catalyst is added after ultrasonication. After degassing, the mixture is reacted at 20-60°C, and after the reaction, the mixture is centrifuged, washed and dried to obtain a Vinyl-COF material.

[0014] (2) Preparation process of X% PILs@COF composite material:

[0015] The prepared Vinyl-COF material is added to an appropriate amount of solvent, and then the prepared functionalized ionic liquid and initiator azobisisobutyronitrile are added, reacted at 50-100°C for 6-48h, cooled to room temperature, filtered, and the filter cake is washed and dried to obtain a novel PILs@COF composite material.

[0016] In the preparation process of the PILs@COF composite material, the functionalized ionic liquid can be 1-(2-carboxyethyl)-3-vinylimidazolium bromide, 1-(2-hydroxyethyl)-3-vinylimidazolium ammonium bromide, 1-(2-aminoethyl)-3-vinylimidazolium ammonium bromide, 1-vinyl-3-ethylimidazolium bromide, and the mass ratio of the ionic liquid to Vinyl-COF is 0.15 to 0.65.

[0017] In the preparation process of the PILs@COF composite material, the solvent used can be one of acetonitrile, acetone, methanol and ethanol.

[0018] In the preparation process of Vinyl-COF material, the reaction solvent used can be one of dioxane / mesitylene, o-dichlorobenzene / n-butanol, and o-dichlorobenzene / benzyl alcohol, and the ratio of the mixed solution is 1 to 1 / 6.

[0019] In the preparation process of the Vinyl-COF material, the washing solvent used can be one or two of tetrahydrofuran, acetone, ethanol, methanol, and dichloromethane.

[0020] This type of composite material can be used in the cycloaddition reaction of epoxy compounds and carbon dioxide: add the material to the epoxy compound, then introduce carbon dioxide to a certain pressure, react at 25°C-150°C for 6-24h, filter after cooling, and analyze the reaction conversion rate and selectivity of the filtrate by GC. The molar ratio of epoxy to the composite material is 5-50:1. The epoxy compound used can be one of epichlorohydrin, epoxystyrene, propylene oxide, methyl propylene oxide, epibromopropane, 1,2-butylene oxide, and 1,2-hexene oxide.

[0021] Comparative Example:

[0022] Preparation of Vinyl-COF catalyst and catalytic performance test:

[0023] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) were placed in a Schlenk tube, 2 mL of mixed solvent (dioxane / mesitylene, 1 mL / 1 mL) was added, 2.4 mg of scandium trifluoromethanesulfonate was added after ultrasonication, ultrasonication was repeated, degassed three times and placed at room temperature for one day, centrifuged with tetrahydrofuran, and dried at 60°C overnight.

[0024] Weigh 0.6 mL of epichlorohydrin and 30 mg of COF catalyst into a 50 mL autoclave, replace the atmosphere with nitrogen three times, then introduce 1 MPa CO2. After sealing, heat to 100 °C and react for 12 h. After cooling, filter. The filtrate was analyzed by gas chromatography, with a conversion rate of 7.57% and a yield of 7.57%.

[0025] Embodiment 1:

[0026] Preparation and catalytic performance test of 35% PIL-1@COF catalyst:

[0027] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 2mL of mixed solvent (dioxane / mesitylene, 1mL / 1mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with tetrahydrofuran and dry at 60℃ overnight. Weigh 14mg Vim-NH2 and disperse it in 10ml acetonitrile, stir for a while, add 26mg COF, stir for a while, add 10mg AIBN, react at 90℃ for 24h under N2 conditions, wash with methanol, and dry at 60℃ overnight.

[0028] 0.6 mL of epichlorohydrin and 30 mg of 35% PIL-1@COF catalyst were weighed into a 50 mL autoclave. After nitrogen replacement three times, 1.2 MPa CO2 was introduced. After sealing, the temperature was raised to 100 °C and the reaction was carried out for 12 h. After cooling, the filtrate was filtered. The filtrate was analyzed by gas chromatography, and the conversion rate was 92.27% and the yield was 91.35%.

[0029] Embodiment 2:

[0030] Preparation and catalytic performance test of 45% PIL-1@COF catalyst:

[0031] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 7mL of mixed solvent (o-dichlorobenzene / n-butanol, 1mL / 6mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with acetone and dry at 60℃ overnight. Weigh 18mgVim-NH2 and disperse it in 10ml acetone, stir for a while, add 22mg COF, stir for a while, add 10mg AIBN, react at 90℃ for 24h under N2 conditions, wash with acetone, and dry at 60℃ overnight.

[0032] Weigh 0.6 mL of epibromopropane and 30 mg of 45% PIL-1@COF catalyst into a 50 mL autoclave. After nitrogen replacement three times, introduce 1 MPa CO2. After sealing, heat to 150 ° C and react for 12 h. After cooling, filter. The filtrate is analyzed by gas chromatography, the conversion rate is 95.15%, and the yield is 94.2%.

[0033] Embodiment 3:

[0034] Preparation and catalytic performance test of 65% PIL-1@COF catalyst:

[0035] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 4mL of mixed solvent (o-dichlorobenzene / benzyl alcohol, 1mL / 3mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with ethanol and dry at 60℃ overnight. Weigh 26mg of Vim-NH2 and disperse it in 10ml of ethanol, stir for a while, add 14mg of COF, stir for a while, add 10mg of AIBN, react at 90℃ for 24h under N2 conditions, wash with ethanol, and dry at 60℃ overnight.

[0036] Weigh 0.6 mL of propylene oxide and 30 mg of 65% PIL-1@COF catalyst into a 50 mL autoclave. After nitrogen replacement three times, introduce 1 MPa CO2. After sealing, heat to 25 °C and react for 12 h. After cooling, filter. The filtrate is analyzed by gas chromatography, the conversion rate is 25.58%, and the yield is 25.32%.

[0037] Embodiment 4:

[0038] Preparation and catalytic performance test of 15% PIL-1@COF catalyst:

[0039] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 2mL of mixed solvent (dioxane / mesitylene, 1mL / 1mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with methanol and dry at 60℃ overnight. Weigh 6mg of Vim-NH2 and disperse it in 10ml of methanol, stir for a while, add 34mg of COF, stir for a while, add 10mg of AIBN, react at 90℃ for 24h under N2 conditions, wash with methanol, and dry at 60℃ overnight.

[0040] 0.6 mL of methyl propylene oxide and 30 mg of 15% PIL-1@COF catalyst were weighed into a 50 mL autoclave. After nitrogen replacement three times, 0.5 MPa CO2 was introduced. After sealing, the temperature was raised to 35 °C and reacted for 24 h. After cooling, the filtrate was filtered. The filtrate was analyzed by gas chromatography, and the conversion rate was 32.5% and the yield was 32.17%.

[0041] Embodiment 5:

[0042] Preparation and catalytic performance test of 25% PIL-1@COF catalyst:

[0043] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 2mL of mixed solvent (dioxane / mesitylene, 1mL / 1mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with methanol and dry at 60℃ overnight. Weigh 10mg Vim-NH2 and disperse it in 10ml methanol, stir for a while, add 30mg COF, stir for a while, add 10mg AIBN, react at 90℃ for 24h under N2 conditions, wash with methanol, and dry at 60℃ overnight.

[0044] 0.6 mL of styrene oxide and 30 mg of 25% PIL-1@COF catalyst were weighed into a 50 mL autoclave. After nitrogen replacement three times, 1 MPa CO2 was introduced. After sealing, the temperature was raised to 100 °C and the reaction was carried out for 6 h. After cooling, the filtrate was filtered. The filtrate was analyzed by gas chromatography, and the conversion rate was 42.37% and the yield was 41.95%.

[0045] Embodiment 6:

[0046] Preparation and catalytic performance test of 55% PIL-1@COF catalyst:

[0047] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 2mL of mixed solvent (dioxane / mesitylene, 1mL / 1mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with methanol and dry at 60℃ overnight. Weigh 22mg of Vim-NH2 and disperse it in 10ml of methanol, stir for a while, add 18mg of COF, stir for a while, add 10mg of AIBN, react at 90℃ for 24h under N2 conditions, wash with methanol, and dry at 60℃ overnight.

[0048] Weigh 0.6 mL of epichlorohydrin and 30 mg of 25% PIL-1@COF catalyst into a 50 mL autoclave. After nitrogen replacement three times, introduce 1 MPa CO2. After sealing, heat to 100 °C and react for 12 h. After cooling, filter. The filtrate is analyzed by gas chromatography, the conversion rate is 82.04%, and the yield is 81.22%.

[0049] Embodiment 7:

[0050] Preparation and catalytic performance test of 35% PIL-2@COF catalyst:

[0051] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 2mL of mixed solvent (o-dichlorobenzene / benzyl alcohol, 1mL / 3mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with ethanol and dry at 60℃ overnight. Weigh 14mg of Vim-OH and disperse it in 10ml of ethanol, stir for a while, add 26mg of COF, stir for a while, add 10mg of AIBN, react at 90℃ for 24h under N2 conditions, wash with ethanol, and dry at 60℃ overnight.

[0052] Weigh 0.6 mL of epoxypropene bromide and 30 mg of 65% PIL-2@COF catalyst into a 50 mL autoclave. After nitrogen replacement three times, introduce 1 MPa CO2. After sealing, heat to 25 °C and react for 12 h. After cooling, filter. The filtrate is analyzed by gas chromatography, the conversion rate is 48.32%, and the yield is 47.84%.

[0053] Embodiment 8:

[0054] Preparation and catalytic performance test of 35% PIL-3@COF catalyst:

[0055] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 2mL of mixed solvent (dioxane / mesitylene, 1mL / 1mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with methanol and dry at 60℃ overnight. Weigh 15mgVim-COOH and disperse it in 10ml methanol, stir for a while, add 85mg COF, stir for a while, add 10mg AIBN, react at 90℃ for 24h under N2 conditions, wash with methanol, and dry at 60℃ overnight.

[0056] Weigh 0.6 mL of 1,2-epoxyhexane and 30 mg of 15% PIL-3@COF catalyst into a 50 mL autoclave. After nitrogen replacement three times, introduce 1 MPa CO2. After sealing, heat to 100 °C and react for 12 h. After cooling, filter. The filtrate is analyzed by gas chromatography, the conversion rate is 44.63% and the yield is 44.18%.

[0057] Embodiment 9:

[0058] Preparation and catalytic performance test of 35% PIL-4@COF catalyst:

[0059] Preparation of COF with 2,5-divinylterephthalaldehyde as ligand: Place a certain ratio of 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine (3:2) in a Schlenk tube, add 2mL of mixed solvent (dioxane / mesitylene, 1mL / 1mL), add 2.4mg of scandium trifluoromethanesulfonate after ultrasonication, ultrasonicate again, degas three times and place at room temperature for one day. Centrifuge with tetrahydrofuran and dry at 60℃ overnight. Weigh 18mg of vimBr and disperse it in 10ml of acetonitrile, stir for a while, add 22mg of COF, stir for a while, add 10mg of AIBN, react at 90℃ for 24h under N2 conditions, wash with methanol, and dry at 60℃ overnight.

[0060] Weigh 0.6 mL of 1,2-butylene oxide and 30 mg of 35% PIL-4@COF catalyst into a 50 mL autoclave. After nitrogen replacement three times, introduce 1 MPa CO2. After sealing, heat to 100 °C and react for 12 h. After cooling, filter. The filtrate is analyzed by gas chromatography, the conversion rate is 61.02% and the yield is 60.41%. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 As comparative examples, XRD patterns of COFs prepared by the solvothermal method in Examples 1, 7 and 8 are shown.

[0062] Figure 2 This is the infrared spectra of the ionic liquids obtained in Example 1, Example 8 and Example 9, where 900-1000 indicates the peak of the vinyl group.

[0063] Figure 3 The infrared spectra of the modified catalysts in Example 1, Example 7, Example 8 and Example 9 show that compared with the single ionic liquid, the 900-1000 vinyl groups disappear, proving that the ionic liquid polymerization is successful. The peaks at 600-700 and 1371 are the peaks of the imidazole ring, and their appearance in the modified catalysts proves that the composite material synthesis is successful.

[0064] Figure 4 The gas chromatography analysis spectra of Example 1, Example 2 and Example 6 are shown.

[0065] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. The present invention proposes a novel PILs@COF composite material, the structural formula of which is shown below: Where R is one of -NH2, -COOH, -OH, -H, and X=Br The composite material exhibits good catalytic performance in the cycloaddition reaction of epoxides and carbon dioxide.

2. The method for preparing a PILs@COF composite material according to claim 1, characterized in that: The following steps are involved: (1) Preparation process of Vinyl-COF material: 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)triazine are mixed and added into a mixed solvent, and a catalyst of scandium trifluoromethanesulfonate is added after ultrasonication, and the mixture is reacted at 20-60°C after degassing, and the reaction is centrifuged, washed and dried to obtain a Vinyl-COF material after the reaction is completed. (2) Preparation process of X% PILs@COF composite material: The prepared Vinyl-COF material is added to an appropriate amount of solvent, and then an ionic liquid and an initiator azobisisobutyronitrile are added, reacted at 50-100° C. for 6-48 hours, cooled to room temperature, filtered, and the filter cake is washed and dried to obtain a novel PILs@COF composite material.

3. In the preparation process of the PILs@COF composite material as described in claim 2, the ionic liquid can be one of 1-(2-carboxyethyl)-3-vinylimidazolium bromide ([CAVIM]Br), 1-(2-hydroxyethyl)-3-vinylimidazolium bromide ([HEVIM]Br), 1-(2-aminoethyl)-3-vinylimidazolium bromide ([AEVIM]Br), and 1-vinyl-3-ethylimidazolium bromide ([EVIM]Br), and the mass ratio of the ionic liquid to the Cinyl-COF material is 0.15 to 0.

65.

4. In the preparation process of the PILs@COF composite material as claimed in claim 2, the solvent used can be one of acetonitrile, acetone, methanol and ethanol.

5. In the preparation process of the Vinyl-COF material as claimed in claim 2, the reaction solvent used can be one of dioxane / mesitylene, o-dichlorobenzene / n-butanol, and o-dichlorobenzene / benzyl alcohol, and the ratio of the mixed solution is 1 to 1 / 6.

6. In the preparation process of the Vinyl-COF material as claimed in claim 2, the washing solvent used can be one or two of tetrahydrofuran, acetone, ethanol, methanol and dichloromethane.

7. As shown in claim 1, the composite material can be used to catalyze the cycloaddition reaction of epoxy compounds and carbon dioxide. It is characterized in that: The material is added to the epoxy compound, and then carbon dioxide is introduced to a pressure of 0.5-1.2 MPa, and the reaction is carried out at 25°C-150°C for 6-24 hours, and the reaction is filtered after cooling, and the filtrate is analyzed for reaction conversion rate and selectivity by gas phase. The molar ratio of the epoxy compound to the composite material is 5-50:

1.

8. As shown in claim 7, the epoxy compound used can be one of epichlorohydrin, styrene oxide, propylene oxide, methyl epoxypropane, and ethyl epoxypropane.

Citation Information

Patent Citations

  • Polymer loaded with ion liquid, preparation and application thereof

    CN101280042A

  • Imine coupled covalent organic framework material and preparation method and application thereof

    CN106967216A

  • Imide covalent organic framework material and preparing method and application thereof

    CN109776814A

  • Preparation of polyionic liquid functionalized MOFs material and application of polyionic liquid functionalized MOFs material in synthesis of isopulegol

    CN112592485A

  • Metal coordination triazine polyionic liquid catalyst as well as preparation method and application thereof

    CN112973797A